2016
DOI: 10.17795/semj41149
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Based on Personality Characteristics in Medical Students

Abstract: Background: The Internet has become a fundamental part of modern life, it has given rise to various problematic behaviors. Some of these behaviors, such as prolific use of social media, frequent email checking, excessive online gaming, online buying and gambling, and viewing pornography cause significant impairment in everyday functioning of some individuals. Different researchers studied psychological aspects like impulsive compulsive spectrum, anxiety and depression in internet addicts. Objectives: The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
2
12
0
Order By: Relevance
“…The classification of Internet addiction as a behavioral disorder remains a controversial matter. It has been described as an individual's uncontrollable and compulsive use of the Internet, which negatively affects academic and job performances, reduces sleep and hygiene quality, and leads to reduced interpersonal social relationships (Lyvers, Karantonis, Edwards, & Thorberg, 2016;Sahraian, Hedayati, Mani, & Hedayati, 2016;Young, 2015;Zhang et al, 2015). Furthermore, the conceptual model of Internet addiction incorporates tolerance, withdrawal, relapse, salience, conflict and mood modification as the core criteria for symptoms of addictive behavior (McNicol & Thorsteinsson, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification of Internet addiction as a behavioral disorder remains a controversial matter. It has been described as an individual's uncontrollable and compulsive use of the Internet, which negatively affects academic and job performances, reduces sleep and hygiene quality, and leads to reduced interpersonal social relationships (Lyvers, Karantonis, Edwards, & Thorberg, 2016;Sahraian, Hedayati, Mani, & Hedayati, 2016;Young, 2015;Zhang et al, 2015). Furthermore, the conceptual model of Internet addiction incorporates tolerance, withdrawal, relapse, salience, conflict and mood modification as the core criteria for symptoms of addictive behavior (McNicol & Thorsteinsson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From the time Internet addiction was first described almost 20 years ago as a clinical disorder (Young, 1998), many studies -also done with university students -have subsequently been conducted on several psychological correlates (Al-Gamal, Alzayyat, & Ahmad, 2016;Burnay, Billieux, Blairy, & Larøi, 2015;Chou et al, 2015;Monacis, de Palo, Griffiths, & Sinatra, 2017). On the other hand, other studies have focused, in relation to Internet addiction, on the following topics: personality traits and other risk factors (Kayiş et al, 2016;Li et al, 2017;Öztürk, Bektas, Ayar, Özgüven Öztornacı, & Yağcı, 2015;Sahraian et al, 2016;Servidio, 2014); and overweight socially stigmatized adolescents (Gentile, Servidio, Caci, & Boca, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Agreeableness and IA were negatively correlated, with only one study showing a positive correlation (Celik et al, 2012). However, the relationship between agreeableness and IA was not significant, even though some studies indicated that they believed the relationship to be quite significant (Olowodunoye et al, 2017;Sahraian et al, 2016;Saini et al, 2016;Stead & Bibby, 2017;Stodt et al, 2018;Zhou et al, 2017Zhou et al, , 2016.…”
Section: Discussionmentioning
confidence: 90%
“…However, the contribution of personality to IA has been the subject of considerable debate, with some research finding that personality had a meaningful relationship with IA and should be used in initial IA prevention screening (Celik, Atak, & BaŞAl, 2012;Sahraian, Hedayati, Mani, & Hedayati, 2016) and others finding the opposite. Buckner et al 2012assessed 170 employees and found that the FFM did not predict pathological Internet use; therefore, the role of personality as an IA predictive factor remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, simulation videos, PowerPoint presentations and online slides provide a more precise, unambiguous and elaborate view of the topic under study. [7][8][9][10] Despite several advantages of the internet described above, many adverse effects are becoming more apparent. These involve economic issues such as income spent on internet subscriptions, time spent on internet surfing; mental health problems like anxiety, depression, broken relationships and loss of work.…”
Section: Introductionmentioning
confidence: 99%